Capturing schizophrenia-like prodromal symptoms in a spinocerebellar ataxia-17 transgenic rat. (April 2017) - Amato, Davide; Canneva, Fabio; Nguyen, Huu Phuc; Bauer, Peter; Riess, Olaf; von Hörsten, Stephan; Müller, Christian P
Rationale: The polyglutamine disease spinocerebellar ataxia type 17 (SCA17) is a neurodegenerative disease leading to severe neurological symptoms during development. Additionally, patients affected by SCA17 display psychosis earlier than their motor disorders. Objective: Here the putative psychotic phenotype and endophenotype of transgenic SCA17 rats was examined. Methods: The expression of schizophrenia-like symptoms was evaluated over a longitudinal period before and after the onset of neurological symptoms in SCA17. To this end, transgenic SCA17 rats' monoamine neurotransmission was investigated along with their locomotion at baseline and in response to amphetamine using in-vivo microdialysis in free moving conditions, their sensorimotor gating using pre-pulse inhibition of startle reaction, and their object memory using the novel object recognition test as an index of cognitive impairments. Results: Presymptomatic SCA17 rats displayed dysregulated monoamine levels at baseline and in response to amphetamine compared with control wild-type (wt) rats. At that stage, neither amphetamine-induced hyperlocomotion nor sensorimotor gating differed from that in wt rats. Symptomatic SCA17 rats developed sensorimotor gating deficits and also showed an impaired object memory, while their monoaminergic responses remained supersensitive to amphetamine. Conclusions: The data of the present study demonstrate a neurochemical endophenotype in SCA17 rats resembling that of prodromal schizophrenia. These findings suggest that a sensitization of the monoamine systems arises early in adulthood in SCA17 rats and may predispose them to express schizophrenia-like symptoms later in life.